Formal reasoning ability, prior knowledge and abstract achievement in the learning of Meiosis and genetics - Zaman, Sara (2008)
The aim of this thesis is to understand the learning of Meiosis and Mendelian genetics by polytechnic students in Singapore, and in particular to identify any misconceptions in these areas that the students may be harbouring. Two strategies were employed in order to investigate this. The first strategy required the construction of a Genetics multiple-choice question (MCQ) test. The 52-item Genetics MCQ test was administered to 75 students as a pre- and post-test. Item analysis indicated that 7 items on the 52-item Genetics MCQ test were either too difficult (Ql), too easy (Q36), or had outlier-sensitive mean square fit statistics (Q18, Q19, Q20, Q29, Q35). Interestingly, analysis of students' responses to Ql indicated that there existed misconceptions regarding the terminology used to describe chromosome structure (such as chromatid, kinetochore, telomere, and centomere).